The New multinationals : Spanish firms in a global context - Guillaen, Mauro F.; Garcâia-Canal, Esteban (Cambridge University Press, 2010)
"A new breed of multinational companies is reshaping competition in global industries. For most of the 19th and 20th centuries, multinational firms came from the most technologically advanced countries in the world. Over the last two decades, however, new multinational firms from upper-middle-income economies such as Spain, Ireland, Portugal, South Korea or Taiwan, emerging economies like Brazil, Chile, Mexico, China, India or Turkey, developing countries such as Egypt, Indonesia or Thailand, and oil-rich countries like the United Arab Emirates, Nigeria, Russia or Venezuela have become formidable global competitors. These firms do not necessarily possess technological or marketing skills. This disadvantage, however, did not prevent them from expanding around the world. In contrast to the classic multinationals, they found strength in their ability to organize, manage, execute, and network. They pursued a variety of strategies of vertical integration, product diversification, learning by doing, exploration of new capabilities, and collaboration with other firms. This book documents the dimensions of this phenomenon, identifies the key capabilities of the new multinationals, and provides a new conceptual framework to understand its causes and implications"--Provided by publisher.